Lipofection of Non-integrative CRISPR/Cas9 Ribonucleoproteins in Male Germline Stem Cells: A Simple and Effective Knockout Tool for Germline Genome Engineering - Obermeier, Mariella; Vadolas, Jim; Verhulst, Stefaan; Goossens, Ellen; Baert, Yoni (Frontiers in Cell and Developmental Biology, 2022)
Gene editing in male germline stem (GS) cells is a potent tool to study spermatogenesis and to create transgenic mice. Various engineered nucleases already demonstrated the ability to modify the genome of GS cells. However, current systems are limited by technical complexity diminishing application options. To establish an easier method to mediate gene editing, we tested the lipofection of site-specific Cas9:gRNA ribonucleoprotein (RNP) complexes to knockout the enhanced green fluorescent protein (Egfp) in mouse EGFP-GS cells via non-homologous end joining. To monitor whether gene conversion through homology-directed repair events occurred, single-stranded oligodeoxynucleotides were co-lipofected to deliver a Bfp donor sequence. Results showed EGFP knockout in up to 22% of GS cells, which retained their undifferentiated status following transfection, while only less than 0.7% EGFP to BFP conversion was detected in gated GS cells. These data show that CRISPR/Cas9 RNP-based lipofection is a promising system to simply and effectively knock out genes in mouse GS cells. Understanding the genes involved in spermatogenesis could expand therapeutic opportunities for men suffering from infertility.